Parent’s Assistance Program in UKGS Toward The Changes of Students’ Oral Hygiene Status - Wirza Wirza; Supriyana Supriyana; Irma Siregar (Jurnal Riset Kesehatan, 2014)
The research objective is analyze the effect of parent’s assistance programme in UKGS toward the changes of students’ oral hygiene status. This study used a Quasi Experiment with pre and post test approach. The sampling technique was purposive sampling, the samples were 68 parents and 68 students. The intervention to the parents was application of parent’s assistance program on the other hard, the interventions to students are measuring OHIS and PHP-M, giving  questionnaire on knowledge, attitudes, actions and mentoring parents. The data were analysed using descriptive statistics, and paired t-test. There were is influence parents assistance program toward the changes of PHP-M, OHIS and mentoring with a significance of ρ-value less than 0.05. Incresing the optimalization of UKGS program is needed a colaboration among puskesmas, scool and studens parent’s to achieve the optimal dental health status among students